RUFINETTI, Edgar J. (2018). La racionalidad práctica en el debate Habermas-Gadamer, Villa María: Eduvim. 372 pp. - Breuer, Marcos (Daimon Revista Internacional de Filosofia, 2021)
Reseña de: RUFINETTI, Edgar J. (2018). La racionalidad práctica en el debate Habermas-Gadamer, Villa María: Eduvim. 372 pp.